A Binder Free and High Sulfur Loaded Three-Dimensional Carbon Nanotubes Electrode for High Performance Li-S Batteries. (7th July 2017) - Patel, Mumukshu D.; Cha, Eunho; Choi, Wonbong
Abstract : Rechargeable Li-S batteries represent advanced battery system offering high energy density with low cost cathode material compared to currently available Li-ion batteries. The critical limitations are mainly associated with the insulating nature of sulfur (5 x 10 -30 S/m), and shuttle effect involving polysulfides (Li2 Sx ; 2<x<8) during charge/discharge process resulting in capacity fading and low cycling stability. Most of the previous strategies suggest entrapment of these polysulfides considering the areal density of the sulfur in the cathode to be less than 2mg/cm 2 . However, to compete with the electrochemical performance of available state-of-the art Li-ion batteries, the sulfur loading amount must be incremented substantially (>6mg/cm 2 ). Here, we develop a simple and facile binder free approach to increase the sulfur loading amount from ~3mg/cm 2 (~40wt.% S) to ~9mg/cm 2 (~60wt.%S) in three-dimensional carbon nanotubes (3D CNTs). The parameters influencing cathode performance were investigated and provide a detail electrochemical analysis for improving the performance of Li-S batteries.